“Good Militias” for Trump: Race, Religion, and Legitimacy in the Modern Militia Movement - Berry, Damon T. (Religions, 2023)
Since the mid-1990s, the popular perception of the militia movement in the United States has associated it with racism and far-right expressions of Christianity. There are good reasons for this assessment, though the movement is more complex than such generalizations suggest. In this article, I describe how Oath Keepers mobilized the image of a “good militia” seeking broader legitimacy and how their efforts have often been damaged by troubling and even criminal elements in their organization, which included militant efforts to keep Trump in power by attempting to subvert the 2020 election. I further argue that public revelations of the group’s racialized discourses and activities, allegations of domestic abuse against its founder, and the recent convictions related to 6 January, including seditious conspiracy, further challenge this effort at legitimization and have thrown the organization into disarray. Moreover, I argue though broader legitimacy may be now out of reach for this fragmented and isolated organization, they may yet find legitimacy among Christian nationalists who have come to conclude that political violence is potentially necessary to save America.